Who Stands Up? Social Psychological Perspectives of Bias-Based Bullying Among LGBTQ+ Youth: The Role of Bystanders - António, R.; Guerra, R.; Cameron, L.; Moleiro, C. (Exploring Identity, Diversity and Stigma in LGBTQ+ Lives, 2027)
This cutting-edge book provides a comprehensive overview of up-to-date research in the field of social psychology of gender identity and sexual orientation. The book is unique in considering perspectives from both dominant and marginalized groups. It illustrates how LGBTQ+ individuals conceptualize gender identity and sexual orientation and their intersections with other social categories. At the same time, the book examines how the dominant group (heterosexual cisgender individuals) forms impressions and interacts with LGBTQ+ people and how these people navigate social norms, expectations, and stigma. Across the different chapters, the book examines the experiences of stigma in different life stages and contexts and maps out the different ways in which stigma manifests and impacts the lives of LGBTQ+ individuals. The book also addresses strategies to reduce stigma and provides solid and contemporary evidence-based knowledge to pave the way for a more inclusive future. Offering a way to better understand the similarities and differences in the experiences of gender and sexual minorities from a social psychological perspective, this book will be essential reading for students and researchers in the fields of gender and sexualities, social psychology, sociology. It will also appeal to equity, diversity, and inclusion (EDI) consultants looking for research-informed resources, health professionals, and anyone interested in knowing more about LGBTQ topics.